Pengaruh Dukungan Sosial Terhadap Efektivitas Bimbingan Kepribadian Klien Pemasyarakatan Tindak Pidana Narkotika - Mico Jeje Saputra; Ali Muhammad (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Correctional clients are correctional inmates who are undergoing a period of guidance outside the correctional institution. In its implementation, community clients are under the supervision of a community counselor to receive guidance, supervision and mentoring. Clients of narcotics crimes have the stigma of being negative or naughty individuals, this is because many narcotics users are found to be someone who has promiscuous relationships and carries out actions that are contrary to religious and societal norms. So personality guidance becomes a very important thing for narcotics crime clients. Social support was identified as a key factor influencing an individual's progress and success in overcoming the challenges of rehabilitation and reintegration into society. Social support provided by family, friends and the community environment is considered capable of increasing the effectiveness of counseling correctional clients. This research aims to determine the effect of social support on the effectiveness of personality guidance for narcotics crime correctional clients. This research uses a literature review study method with the technique of collecting and reviewing various relevant sources such as previous research.